Serologic and Molecular Evidence of Vaccinia Virus Circulation among Small Mammals from Different Biomes, Brazil - Júlia B. Miranda; Iara A. Borges; Samantha P.S. Campos; Flávia N. Vieira; Tatiana M.F. de Ázara; Fernanda A. Marques; Galileu B. Costa; Ana Paula M.F. Luis; Jaqueline S. de Oliveira; Paulo César P. Ferreira; Cláudio Antônio Bonjardim; Silvio L.M. da Silva; et al. (Emerging Infectious Diseases, 2017)
Vaccinia virus (VACV) is a zoonotic agent that causes a disease called bovine vaccinia, which is detected mainly in milking cattle and humans in close contact with these animals. Even though many aspects of VACV infection have been described, much is still unknown about its circulation in the environment and its natural hosts/reservoirs. To investigate the presence of Orthopoxvirus antibodies or VACV DNA, we captured small rodents and marsupials in 3 areas of Minas Gerais state, Brazil, and tested their samples in a laboratory. A total of 336 animals were tested; positivity ranged from 18.1% to 25.5% in the 3 studied regions located in different biomes, including the Atlantic Forest and the Cerrado. Analysis of nucleotide sequences indicated co-circulation of VACV groups I and II. Our findings reinforce the possible role played by rodents and marsupials in VACV maintenance and its transmission chain.